Correlation between Family Support and Dietary Adherence in Patients with Type 2 Diabetes Mellitus - Munir, Nurwahyuni; Putri, Helmalia; Safruddin (Omni Nursing Journal, 2026)
Background: Type 2 diabetes mellitus is a metabolic disorder characterized by hyperglycemia due to insulin resistance and/or insufficient insulin secretion. The disease is often linked to risk factors such as obesity, lack of physical activity, and an unhealthy diet. Family support can influence the patient to make decisions in the implementation of the diet according to the previous studies; however, little is known the correlation of these variables in the local context of South Sulawesi. Objective: The purpose of this study was to determine the relationship between family support and dietary adherence of type 2 diabetes mellitus patients. Methods: The research design used was an analytical survey with a cross-sectional study approach with quantitative research methods. Sociodemographic questionnaire, family support questionnaire, and dietary adherence questionnaire were utilized in this study. The Chi-Square test was employed to analyze the correlation between family support and dietary adherence of patients with type 2 diabetes mellitus. Lemeshow formula was used to determine the sample size. Results: A total of 67 respondents participated in this study. Majority of respondents had low dietary adherence, which accounted for 43 respondents (64.2%) and most respondents had good family support, consisting of 39 respondents (58.2%). According to the Chi Square test, there was a significant correlation between family support and dietary adherence in patients with type 2 diabetes mellitus, with a p-value of 0.001. Conclusion: Family support is associated with dietary adherence of patients with type 2 diabetes mellitus. Therefore, health professionals need to encourage family to provide support to type 2 diabetes mellitus patients to improve the health outcome of the patients.